2016
DOI: 10.1590/1983-1447.2016.04.65022
|View full text |Cite
|
Sign up to set email alerts
|

Utilidade da teoria do conforto para o cuidado clínico de enfermagem à puérpera: análise crítica

Abstract: The theory can be used to support and improve clinical nursing care for postpartum women, and help improve puerperal comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 2 publications
1
8
0
7
Order By: Relevance
“…In their narratives, it was observed the importance they give to the teaching of theories as scientific contribution to their actions. This perception of the participants is in line with the results of other studies, with this research as a motto (4,5,13) . All participants reported that, even if only superficially, at some point in their professional training, they had contact with at least one nursing theory.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In their narratives, it was observed the importance they give to the teaching of theories as scientific contribution to their actions. This perception of the participants is in line with the results of other studies, with this research as a motto (4,5,13) . All participants reported that, even if only superficially, at some point in their professional training, they had contact with at least one nursing theory.…”
Section: Discussionsupporting
confidence: 92%
“…Given its characteristics, nursing theories develop concepts, models, and assumptions applicable in practice and that facilitate professional activities, justifying the importance of supporting daily care in theories that have applicability, assist the population, and subsidize care (4) . Their use provides scientific character to the profession (9,12) , strengthens the care process, and favors actions directed at the human being, within a certain context, contributing to restore their health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para a teórica, o conforto pressupõe ausência de preocupação, dor, sofrimento, entre outros, como causa ou efeito de desconforto, é o contrário de desconforto. Portanto torna-se relevante para ser aplicada a parturiente, por meio destas que o enfermeiro obstetra e sua equipe promovem interação, vínculo efetivo, confiança, esperança, consolo, apoio, encorajamento e cuidado de qualidade (LIMA, et al, 2016).…”
Section: Introductionunclassified
“…Em sua Teoria do Conforto Kocalba refere-se à transcendência como a busca de estar acima dos problemas ou da própria dor para alcançar o estado de bemestar (Lima et al, 2016).…”
Section: Idadeunclassified